Producción de forraje y composición bromatológica del pasto azul (Dactylis glomerata) en asociación con trébol rojo (Trifolium pratense) y alfalfa (Medicago sativa). - Guamangate Chiguano, Alex Ramiro (2022)
This research was developed on the property of Mr. Lorenzo Pilatasig, located in the Chinalo Bajo sector, Chugchilán Parish, Sigchos Canton, Cotopaxi Province. Pastures are characterized as a source of nutritional components in livestock production, by associating pastures and grasses it provides a complete and balanced food providing energy and protein, despite the fact that there is a considerable number of native and introduced forage species, the research was based on three species, bluegrass grasses, red clover, and alfalfa legumes, they are considerably more resistant than other forage grasses in summer and they respond very well to different soil textures. For this reason, the research was centered on evaluating the forage production and bromatological composition of bluegrass (Dactylis glomerata) in association with the red clover (Trifolium pratense) and alfalfa (Medicago sativa). Specific objectives were set to determine the agronomic behavior of the grass association in reference to bluegrass plus red clover and bluegrass plus alfalfa. It would help to know the bromatological composition of blue grass in association with red clover and alfalfa to establish the benefit/cost of the study treatments. The association was made between 70% grass, 30% legume and 100% control, for this reason different treatments were established to evaluate the nutritional composition in the crop, the respective treatments under study had a total of 30 plots of land each. Broadcast sowing was carried out, in addition, it was determined how the relationship of chemical properties of the soil influences the pastures production, and thus the different variables under study were evaluated, such as plant height, basal contour, weight of green forage, analysis of the chemical composition of the soil, analysis of the bromatological composition, and economic analysis. Using a completely randomized block design with five treatments, six repetitions, and the Tukey's test at 5% probability of error, the mixture of blue grass plus red clover presented better results in height, contour and weight, they showed an acelerated growth unlike when associated with alfalfa, the legume presented a slow development, but better protein levels in more days.